Out of the Ground (Into the Sky) - Brad Decker (Journal of the Association for Technology in Music Instruction, 2025)
Out of the Ground (Into the Sky) is written for clarinetist, with computer processing in combination with fixed audio. It is a multilayered performance project, that aims to memorialize a loved one. The performance (by both clarinetist, and the computer) is nuanced and visceral. This is intended to be a memorable concert piece.
Keywords: composition